Effectiveness of Oropharyngeal Exercises on Daytimesleepiness, Snoring and Risk of Obstructive Sleep Apnea Amongadults: Review (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Sleep disorders are very frequent among general population. The prevalence of sleepdisturbances varies between 25 and 45%. Types of sleep abnormalities in which snoring is the commonamong all the adults. Oropharyngeal exercises are new, non-invasive, cost effective treatment modality forindividuals having risk of obstructive sleep apnea, daytime sleepiness and snoring.Methods: The study design was systematic review and it includes studies from databases of PUBMED,MEDLINE, Cochrane library, SCOPUS, Science direct, and Google scholar (2002-2017).Result: Total 14 relevant articles were under taken. Studies included are related to prevalence, assessment, effect of different modalities and oropharyngeal exercises on daytime sleepiness, snoring and risk ofobstructive sleep apnea and excludes those studies that involve other sleep disorders like insomnia,narcolepsy and circadian rhythm disorder etc. Abstracted information is related to their design, populationcharacteristics, intervention and outcomes.Conclusion: Oropharyngeal exercises are effective in reducing the daytime sleepiness, snoring and riskof obstructive sleep apnea among adults having snoring. Several studies came out with the result thatoropharyngeal exercises are beneficial in reducing sleep disorders.